ENVIRONMENTAL DISCOURSE OF THE MEDIA IN SERBIA - Jevtić, Miloš; Spasojevic, Nenad (Political Review, 2026)
The authors of this paper examine the ways in which the media in Serbia have reported on environmental issues, with the aim of identifying their frequency, content structure, and dominant themes in the headlines of print newspapers and online news portals. The relevance of the selected topic is grounded in public opinion research, which has consistently demonstrated a growing level of public interest in issues related to environmental degradation. In other words, environmental problems, climate change, and energy transitions – albeit in different forms and to varying degrees – have gained increasing prominence within the Serbian public sphere. Accordingly, a content analysis was conducted on a sample of articles published in various print media outlets and online portals over the period from 2015 to 2025. The selected time frame enabled insight into the longitudinal relevance of these issues for mass media, reflected in the number of headlines, but also a better understanding of the broader ecological and economic context (the planning of mini-hydropower plant construction, air pollution, the announcement of various mining projects, etc.). The analysis is limited to headlines as the primary carriers of information, given their role in directing readers’ attention in line with their interests. A mixed-methods approach combining quantitative and qualitative analysis was employed in order to capture a broader range of characteristics of media discourse, such as the representation of various environmental issues, the style of reporting and its informational value and the presence of critical or sensationalist framing.
Keywords: environmental issues; media; content analysis; Republic of Serbia